The influence of new heattreated NiTi alloy on shaping ability and apical transportation of maxillary molars. The evaluation of the larger apical preparation on mesiobuccal and distobuccal canals of maxillary molars: a micro-computed study - Camargo, Éricson Janolio de (2018)
The aim of this study was to evaluate canal transportation; centering ability; dentin thickness; change in volume, and time spent on shaping ability of maxillary molars prepared with mechanized NiTi file systems composed of a conventional NiTi alloy (Mtwo), a CM-Wire (Prodesign R and Hyflex CM) NiTi alloy, R-phase (Twisted File Adaptive) and an M-Wire (Reciproc) NiTi alloy]. With the purpose of understanding the role of new treated NiTi alloys in larger apical preparations, this type of preparation was evaluated in the mesiobuccal (MB) and distobuccal canal (DB) of maxillary molars, as well as, in the second mesiobuccal (MB2) canals in extracted maxillary first molars by means of micro-computed tomographic (micro- CT) imaging. For the second mesiobuccal canal (MB2) evaluation, thirty maxillary molars with Vertucci type IV canal configuration were selected and randomly divided into 3 groups (n = 10): Reciproc [REC; VDW, Munich, Germany], Prodesign R [PDR; Easy, Belo Horizonte, Brazil] and Mtwo [MO; VDW, Munich, Germany]. To assess the mesiobuccal and distobuccal canals, a total of 45 extracted maxillary molars were selected according to the following criteria: MB canals exhibiting curvatures according to the Weine classification in the 20-30 degree range; and DB canals presenting curvatures in the 0-5 degree range. These teeth were randomly assigned to three groups, Reciproc (REC) [40.06]; Hyflex CM (HF) [40.06] [Coltene, Cuyahoga Falls, OH, USA] and Twisted file Adaptive (TFA) [35.04]. After root canal preparation, all the teeth were scanned to evaluate parameters previously cited. In particular, the percentage of negotiability of the MB2 canal was evaluated. All parameters were statistically compared using the Kruskal-Wallis and Dunns Multiple comparison tests within groups with a significance level of 5%. For MB2 canals, no statistically significant difference was observed among the three groups with regard to the values of canal transportation, centering ability, remaining dentin thickness in the coronal third, number of specimens with thickness under 0.5 mm in the danger zone, and apical volume (P>0.05). However, the entire volume of the canal in Group MO differed statistically from that of Group PDR (P<0.05), but Group REC did not differ statistically from Groups MO and PDR (P>0.05). Group PDR demanded more time to reach WL than use of the MO and REC systems. For MB and DB canals, the trend of canal transportation was towards inner curvature in apical third, while in the coronal third it was towards the outer curve. There was no difference in apical transportation values in the first apical millimeters for both canals. In MB canal, at 3 and 4 mm, the Reciproc transportation value was significantly lower than that of Hyflex CM(P<0.05). In the DB canal, at 2 and 4 mm, Reciproc showed substantially higher values than Group TFA (P<0.05). There was no statistically significant difference between the two canals among the three systems for centering ability in the apical third and the remaining dentin thickness (RDT). For DB canal, there was no significant difference in shaping time, but in the MB canal, Group TFA was swifter than Reciproc and Hyflex CM. The initial changes in volume (apical/entire) after canal preparation was statistically significant within groups in MB and DB canals for percentage and volume of dentin removed. TFA had the lowest values for the apical and entire volumes of dentin removed in both canals compared with Reciproc and Hyflex CM (P<0.05). TFA had the lowest percentage of dentin removed from the entire MB canal, and from the apical and entire volume of DB canal. For negotiating and shaping the MB2 canal, the three file systems had similar performance. However, the REC system reached the full working length faster than PDR. The MO and REC systems removed more dentin in the inner furcation area when compared with PDR. For MB and BD canals, the heat treated NiTi alloy systems used for larger apical preparation evenly maintained the morphology of the MB and DB canals of maxillary molars. In shaping procedures, the larger apical preparation produced slight canal transportation without evidence of significant preparation errors. However, these variations may not be feasible of clinical significance. Use of TFA was swifter for preparing the MB canal and produced fewer changes in volume parameters. The TFA system was able to preserve the original canal anatomy with less canal transportation than the Reciproc and Hyflex CM systems.